Terahertz Time‐Domain Spectroscopy and Near‐Field Microscopy of Transparent Silver Nanowire Networks. Issue 3 (15th August 2019) - van Hoof, Niels; Parente, Matteo; Baldi, Andrea; Rivas, Jaime Gómez
Abstract: Transparent conductive layers are key components of optoelectronic devices. Here, a polyol method is used to synthesize large quantities of monodisperse silver nanowires (AgNWs) and these are used to fabricate transparent conducting networks over large areas. The optical extinction and terahertz (THz) conductance of these networks are simultaneously investigated, using optical and THz spectroscopy, and THz near‐field microscopy. The combination of optical and THz measurements allows the identification of transparent regions with high conductance. The THz near‐field measurements reveal local variations in the THz transmission and conductance that are averaged in far‐field measurements. These results demonstrate that THz near‐field microscopy is a powerful tool for the quantitative investigation of new conductive transparent electrodes. Abstract : Transparent electrodes are important for optoelectronic devices, such as displays and solar cells. A subdiffraction terahertz microscope is used for determining the AC conductivity of chemically synthetized silver‐nanowire networks without the need of electrical contacts. Terahertz near‐field microscopy shows features that are not resolvable using conventional far‐field methods, which makes this technique a powerful tool for the quantitative investigation of conductive structures.